Estimating conditional treatment effects of EIB lending to SMEs in Europe - Alessandro Barbera; Aron Gereben; Marcin Wolski (European Investment Bank (EIB), 2022)
We estimate heterogeneous treatment effects of the EIB financial support on European firms between 2008 and 2015. The relevant control groups are created with propensity score matching and the effects are estimated in a difference-in-differences framework, controlling for firm-level and country-sector-year fixed effects. We find that the positive effects of EIBsupported lending on job creation and investments were larger for smaller and younger firms. Moreover, we find evidence that longer maturities and more advantageous loan pricing are associated with larger employment and investment effects, while no larger impact is observed for larger loan volumes. Overall, the results suggest that benefits of the EIB support are rather observed on an intensive, rather than on an extensive, margin.
Keywords: 330; climate action and environment; economics